Translational velocity of a charged oil droplet close to a horizontal solid surface under an applied electric field. (April 2019) - Wang, Chengfa; Song, Yongxin; Pan, Xinxiang; Li, Dongqing
Highlights: The interactions between an oil droplet and a horizontal solid surface was analyzed. There is a separation distance between an oil droplet and a solid surface. The droplet and solid surface zeta potentials affect the droplet moving direction. The droplet moving velocity increases with the decrease of the separation distance. Abstract: This work numerically investigated the translational velocity of a negatively charged oil droplet in the water near a negatively charged solid surface under a DC electric field. The equilibrium separation distance between the charged oil droplet and the charged solid surface is calculated under different parameters and the translational motion of the droplet near the solid surface is simulated via a three-dimensional mathematical model. The results indicate that the velocity of the droplet is higher under a larger zeta potential of the solid surface and a smaller zeta potential of the droplet. When the absolute value of the negative zeta potential of the droplet is larger than that of the solid surface, the droplet will move in opposite direction of the electric field. It is also found that the droplet translational velocity increases with the decrease of the separation distance between the oil droplet and the solid surface.